An Analysis of Tourism Impacts on Residents Quality of Life - Mohd Bakri, Norjanah; Jaafar, Mastura (AENSI, 2015)
Tourism development is a global phenomenon impacting the changes of the human life pattern. Tourism development and quality of life have long been studied, mostly from the perspective of how tourism development affects the quality of life. Tourism growth responds to changes in quality of life involving the direct effect of global perceived tourism impact on global perceived quality of life, indirect effect global perceived tourism impacts on global perceived quality of life, through life satisfaction and happiness (material, emotional, community and health and security well-being). Understanding the relationship between tourism development and quality of life will broaden the explanation and goals of development and will help changing the argument from an income and standard of living perspective to a quality of life standpoint. Against this background, this study aims to revisit how the tourism development affects the residents’ quality of life and to review the willingness of society to accept tourism development occurring in their area. Such studies should be conducted as this will help in assessing the level of the development of tourism in bringing a positive change for the benefit and interest of the local communities.